Impact of Chlorella vulgaris and probiotic supplementation on performance, immunity and intestinal microbiota of broiler chickens - Verena Pereira Dinalli; Marcio Carvalho Costa; Emerson José Venâncio; João Antônio Barbosa Filho; José Antônio Bessegatto; Augusto Tasch Holkem; Amauri Alcindo Alfieri; Caio Abercio da Silva; Alexandre Oba (PLoS ONE, 2025)
Chlorella vulgaris has antioxidant, antimicrobial, and anti-inflammatory properties, as well as the probiotic that is important for keeping the intestinal microbiota balanced. The objective was to test the impact of supplementation with microalgae and/or probiotics on broiler chickens’ performance, immunity, and intestinal microbiota. The experimental design was in randomized blocks in a 4x2 factorial scheme, with four levels of inclusion of C. vulgaris (0; 0.25; 0.50 and 1%) associated or not with a commercial probiotic with five replications of 26 chickens per experimental unit. The results showed that probiotics improved feed conversion. Probiotics increased the productivity index only at 0.25% C. vulgaris supplementation. There was a reduction in spleen weight at 42 days of age in chickens fed with probiotics, but the different treatments did not alter serum antibodies. Sampling age had a significant impact on richness addressed by the number of observed genera and diversity addressed by the Shannon index. The most abundant phylum in the chicken intestinal tract was Firmicutes followed by Bacteroidetes and Proteobacteria. Bifidobacterium spp. was found in animals receiving 1% microalgae and probiotics on day 42, suggesting that this genus has benefited from microalgae supplementation. It is concluded that the probiotic and C. vulgaris have the potential to improve performance without causing major changes in the immunity and cecal microbiota.